Renewable CO2 adsorption material based on deoiling residue of oil-based cuttings from shale gas drilling and preparation and regeneration method thereof

By grinding, pickling and alkaline melting the deoilation residue of shale gas drilling oil bedrock chips, renewable CO2 adsorption materials were prepared, solving the problem of failure to effectively utilize deoilation residues in the prior art, and achieving efficient CO2 adsorption and material recycling.

CN119746807APending Publication Date: 2025-04-04PUYANG TIANDIREN ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411935742.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art has failed to effectively utilize shale gas drilling oil bedrock deoilation residues, especially in the preparation of efficient CO2 adsorption materials, and the existing methods require special equipment for regeneration.

Method used

Renewable CO2 adsorption material was prepared by grinding, pickling and alkaline melting residues of shale gas drilling oil bedrock chips, and combining the use of sodium metaaluminate and deionized water. This method performs the recycling of materials under normal pressure environment, avoiding the need for special equipment.

Benefits of technology

It realizes the preparation of highly efficient CO2 adsorbent materials at lower temperatures and shorter time, reduces energy consumption, and realizes the regeneration and utilization of materials through heat treatment, ensuring the recycling and efficient performance of adsorbents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746807A_ABST
    Figure CN119746807A_ABST
Patent Text Reader

Abstract

The present application relates to the field of resource utilization of solid waste, and specifically to a renewable CO2 adsorbent material based on deoiled residue of oil-based rock cuttings from shale gas drilling, and a preparation and regeneration method thereof, wherein the preparation method comprises: first grinding and sieving the deoiled residue to obtain deoiled residue powder; acid washing and centrifuging the deoiled residue powder with an acid solution, washing the precipitate with an alkaline solution to neutrality, and drying to obtain a decontaminated powder; mixing the decontaminated powder with sodium hydroxide, performing a second grinding, roasting and cooling to obtain an alkali-melted product; adding sodium aluminate and deionized water to the alkali-melted product, stirring and standing to collect the precipitate; crystallizing, washing, filtering and drying the precipitate to obtain a renewable CO2 adsorbent material. The method of the present application realizes the resource utilization of deoiled residue, and can complete the regeneration of CO2 adsorbent materials under normal pressure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of solid waste resource utilization, and specifically to a renewable CO2 adsorption material based on shale gas drilling oil-based cuttings deoiling residue and a preparation and regeneration method thereof. Background Art

[0002] Oil-based rock cuttings from shale gas drilling contain a lot of mineral oil. Pyrolysis is an important method for treating oil-based rock cuttings at home and abroad. After treatment, the remaining solid phase - oil-based rock cuttings deoiling residue is finally produced. However, since oil-based rock cuttings deoiling residue may still have biological toxicity, its rational resource utilization has attracted widespread attention. At present, the main resource utilization of oil-based rock cuttings deoiling residue is mainly concentrated in the field of building materials utilization, mainly including cement kiln co-disposal, concrete preparation, brick making, roadbed material preparation, construction ceramsite preparation and other resource processing technologies. Although oil-based rock cuttings deoiling residue can be used as a building material, it is easily restricted by the development of the building materials industry, and the market value of building materials products as a resource is not high.

[0003] As a mineral rich in silicon and aluminum, shale gas drilling oil-based cuttings meet the chemical composition required for the preparation of zeolite molecular sieve adsorbents and can be used as raw materials for zeolite-like adsorbent materials. Using the deoiled residue of shale gas drilling oil-based cuttings to prepare adsorbent materials is one of the ways to convert and utilize them at a high value. Prior art CN201810011878.3 has demonstrated the feasibility of using shale gas oil-based drilling cuttings pyrolysis ash as raw material to prepare zeolite, but it has not verified the adsorption effect of artificial zeolite on CO2. Prior art CN114192122A discloses a regenerable nanoporous adsorbent material for removing carbon dioxide, but it needs to be regenerated in an environment with a vacuum degree of -99kPa, and special equipment needs to be used to achieve a negative pressure environment during its regeneration.

[0004] Therefore, a new method for preparing CO2 adsorbent materials is needed to fill the current technical gap in preparing CO2 adsorbent materials based on deoiling residues and to achieve the recycling of CO2 adsorbent materials without using special equipment. Summary of the invention

[0005] The problem that the present application aims to solve is to provide a renewable CO2 adsorption material based on the deoiling residue of oil-based rock cuttings from shale gas drilling, and a preparation and regeneration method thereof, so as to realize the resource utilization of the deoiling residue and complete the regeneration of the CO2 adsorption material under normal pressure environment.

[0006] In order to solve the above technical problems, this application adopts the following technical solutions:

[0007] On the one hand, the present application provides a method for preparing a renewable CO2 adsorbent material based on shale gas drilling oil-based cuttings deoiling residue, comprising the following steps:

[0008] The de-oiled residue is subjected to a first grinding and sieving, and the sieved powder is collected to obtain a de-oiled residue powder; the de-oiled residue powder is acid-washed and centrifuged with an acid solution, and an acidic precipitate is collected; the acidic precipitate is washed with an alkaline solution to neutrality and then dried to obtain a de-impurity powder; the de-impurity powder is mixed with sodium hydroxide and subjected to a second grinding to obtain an alkali-melt reaction system; the alkali-melt reaction system is calcined and cooled to obtain an alkali-melt product; sodium aluminate and deionized water are added to the alkali-melt product, and the precipitate is collected after stirring and standing; the precipitate is transferred to a reactor, and is crystallized, washed, filtered and dried to obtain the renewable CO2 adsorption material.

[0009] Furthermore, the weight ratio of the impurity-removing powder to the sodium hydroxide is 1:(1.2-1.4).

[0010] Furthermore, the silicon-aluminum ratio in the precipitate is (1-3):1.

[0011] Furthermore, the screening is carried out on a 100-mesh sieve.

[0012] Furthermore, the acid solution includes a hydrochloric acid solution with a mass fraction of 5% to 10%.

[0013] Furthermore, the alkaline solution includes a sodium hydroxide solution with a mass fraction of 10%.

[0014] Furthermore, the pickling temperature is 80-85° C., and the pickling time is 2 hours.

[0015] Furthermore, the calcination temperature is 550-600° C., and the calcination time is 1-3 hours.

[0016] Furthermore, the crystallization temperature is 90 to 110° C., and the crystallization time is 8 to 24 hours.

[0017] Furthermore, the stirring time is 16 to 24 hours.

[0018] Furthermore, the amount of the deionized water used is 1.2 to 1.4 times the sum of the mass of the impurity-removing powder and the sodium hydroxide.

[0019] On the other hand, the present application provides a renewable CO2 adsorption material prepared by the above preparation method.

[0020] In another aspect, the present application provides a renewable CO2 adsorbent material prepared by the above preparation method or a method for regenerating the above renewable CO2 adsorbent material, comprising the following steps:

[0021] The regenerated CO2 adsorbent material is heat-treated at normal pressure to obtain a regenerated CO2 adsorbent material.

[0022] Furthermore, the temperature of the heat treatment is 250° C., and the time of the heat treatment is 60 minutes.

[0023] This application has the following beneficial effects:

[0024] (1) The preparation method provided in the present application has a low crystallization temperature and a short reaction time when using shale gas drilling oil-based rock cuttings to prepare renewable CO2 adsorption materials, which greatly reduces energy consumption;

[0025] (2) This application makes full use of the oil-based rock cuttings produced by shale gas drilling and converts them into non-toxic and harmless renewable CO2 adsorption materials with high market value, which can greatly reduce the emission of oil-based rock cuttings;

[0026] (3) The renewable CO2 adsorbent material prepared in the present application can effectively adsorb CO2, and can restore the adsorption capacity through heat treatment at normal pressure after use, and maintain a high activity, thereby realizing the recycling of the adsorbent. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a process flow chart for preparing renewable CO2 adsorption material based on deoiling residues of shale gas drilling oil-based cuttings in this application. DETAILED DESCRIPTION

[0028] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings, but the protection scope of the present invention is not limited to the following.

[0029] Example 1

[0030] The residue after de-oiling from shale gas drilling oil-based cuttings pyrolysis treatment was used as raw material, and the silicon and aluminum elements in the de-oiled residue were analyzed by XRF. The analysis results are shown in Table 1.

[0031] Table 1

[0032] element Si Al Element percentage (%) 28.331 8.6112

[0033] Example 2

[0034] Follow these steps to prepare the regenerable CO2 adsorbent material:

[0035] S11. The de-oiled residue in Example 1 was crushed and ground using a pulverizer, and then sieved using a 100-mesh sieve, and the sieved powder was collected to obtain a de-oiled residue powder;

[0036] S12. The deoiled residue powder was acid washed with 10% hydrochloric acid at 85°C for 2 h, and then centrifuged at 2000 rpm for 10 min to collect the acid precipitate;

[0037] S13. The acidic precipitate is washed to neutrality with a 10% sodium hydroxide solution and dried to obtain a decontaminated powder;

[0038] S14 take 5g of the impurity-removing powder, add 6g of sodium hydroxide and grind and mix to obtain an alkali melt reaction system;

[0039] S15. The alkali-melt reaction system was placed in a muffle furnace, calcined at 550 ° C for 1 h, and then cooled to room temperature to obtain an alkali-melt product;

[0040] S16. Sodium aluminate was added to the alkali-melted product until Si:Al in the mixture was 1:1, and then 13.2 mL of deionized water was added, and the mixture was stirred and solubilized at room temperature for 16 h. After standing for 30 min, the precipitate was collected;

[0041] S17. The precipitate is transferred to a reactor, and after crystallization in an oven at 100°C for 8 hours, the crystallized product is washed with deionized water until it is neutral, and then filtered. The sample obtained by filtration is placed in an oven at 100°C and dried for 120 minutes to obtain a renewable CO2 adsorption material.

[0042] Example 3

[0043] Follow these steps to prepare the regenerable CO2 adsorbent material:

[0044] S11. The de-oiled residue in Example 1 was crushed and ground using a pulverizer, and then sieved using a 100-mesh sieve, and the sieved powder was collected to obtain a de-oiled residue powder;

[0045] S12. The deoiled residue powder was acid washed with 5% hydrochloric acid at 80°C for 2 h, and then centrifuged at 2000 rpm for 10 min to collect the acid precipitate;

[0046] S13. The acidic precipitate is washed to neutrality with a 10% sodium hydroxide solution and dried to obtain a decontaminated powder;

[0047] S14 take 5g of the impurity-removing powder, add 7g of sodium hydroxide and grind and mix to obtain an alkali-melt reaction system;

[0048] S15. The alkali-melt reaction system was placed in a muffle furnace, calcined at 600 ° C for 2 h, and then cooled to room temperature to obtain an alkali-melt product;

[0049] S16. Sodium aluminate was added to the alkali-melted product until Si:Al in the mixture was 2:1, and then 16.8 mL of deionized water was added, and the mixture was stirred and solubilized at room temperature for 20 h. After standing for 30 min, the precipitate was collected;

[0050] S17. The precipitate is transferred to a reactor, and after crystallization in an oven at 90°C for 24 hours, the crystallized product is washed with deionized water until it is neutral, and then filtered. The sample obtained by filtration is placed in an oven at 100°C and dried for 120 minutes to obtain a renewable CO2 adsorption material.

[0051] Example 4

[0052] Follow these steps to prepare the regenerable CO2 adsorbent material:

[0053] S11. The de-oiled residue in Example 1 was crushed and ground using a pulverizer, and then sieved using a 100-mesh sieve, and the sieved powder was collected to obtain a de-oiled residue powder;

[0054] S12. The deoiled residue powder was acid washed with 5% hydrochloric acid at 80°C for 2 h, and then centrifuged at 2000 rpm for 10 min to collect the acid precipitate;

[0055] S13. The acidic precipitate is washed to neutrality with a 10% sodium hydroxide solution and dried to obtain a decontaminated powder;

[0056] S14. Take 5g of the impurity-removing powder, add 6.5g of sodium hydroxide and grind and mix to obtain an alkali-melt reaction system;

[0057] S15. The alkali melt reaction system was placed in a muffle furnace, calcined at 575 ° C for 3h and then cooled to room temperature to obtain an alkali melt product;

[0058] S16. Sodium aluminate was added to the alkali-melted product until Si:Al in the mixture was 3:1, and then 15 mL of deionized water was added, and the mixture was stirred and solubilized at room temperature for 24 h. After standing for 30 min, the precipitate was collected;

[0059] S17. The precipitate is transferred to a reactor, and after crystallization in an oven at 110°C for 16 hours, the crystallized product is washed with deionized water until it is neutral, and then filtered. The sample obtained by filtration is placed in an oven at 100°C and dried for 120 minutes to obtain a renewable CO2 adsorption material.

[0060] Example 5 Verification of the adsorption effect of the regenerable CO2 adsorbent material on simulated CO2-containing gas

[0061] The regenerable CO2 adsorption material prepared in Examples 2 to 4 was placed in a tubular furnace quartz tube adsorption column, both ends were blocked with quartz wool, and the adsorption temperature was controlled at 30°C by programming the tubular furnace; simulated gas (containing 5% CO2 and 95% N2) was introduced, and the outlet CO2 gas content was measured by gas chromatograph. When the adsorption column was saturated, the CO2 gas concentration in the tail gas was almost equal to the inlet concentration, that is, C / C0=1. The saturated adsorption amount of CO2 q m The following formula is used for calculation and the calculation results are shown in Table 2.

[0062]

[0063] Among them, q m —Saturated adsorption capacity (mg / g);

[0064] F—gas flow rate (m 3 / min);

[0065] m—mass of renewable CO2 adsorption material (g);

[0066] C0—inlet gas concentration (mg / m 3 );

[0067] C—Outlet gas concentration (mg / m 3 );

[0068] t—adsorption time (min).

[0069] Table 2: Adsorption effect of various renewable CO2 adsorbent materials on CO2.

[0070] project Saturated adsorption capacity (mg / g) Example 2 63.21 Example 3 68.34 Example 4 64.72

[0071] According to Table 2, the present application uses the de-oiled residue of shale gas drilling oil-based cuttings as raw material to prepare renewable CO2 adsorbent material. When the slag-alkali ratio is 1:1.4, the silicon-aluminum ratio is 2:1, the roasting temperature is 600°C, the amount of deionized water is 1.4 times that of the molten product, and the crystallization time is 24h, the obtained adsorbent material has the best adsorption effect on CO2. The adsorption amount of the adsorbent when saturated reaches 68.34 mg / g. The renewable CO2 adsorbent prepared in Example 3 is selected for subsequent experiments.

[0072] Example 6 Adsorption effect of regenerable CO2 adsorbent material on CO2 at different temperatures

[0073] 1 g of the renewable CO2 adsorption material prepared in Example 3 was placed in three tubular furnace quartz tube adsorption columns. Both ends were sealed with quartz wool. The adsorption temperatures were controlled by programming the tubular furnace to be 30°C, 50°C, and 100°C, respectively. Simulated gas (containing 5% CO2 and 95% N2) was introduced, and the CO2 content in the outlet gas was analyzed by gas chromatograph. The saturated adsorption amount was calculated. The results are shown in Table 3.

[0074] Table 3: Adsorption effect of regenerable CO2 adsorbent materials on CO2 at different temperatures

[0075] Adsorption temperature (℃) Saturated adsorption capacity (mg / g) 30 68.34 50 47.84 100 18.23

[0076] According to Table 3, the saturated adsorption capacity of CO2 of the renewable CO2 adsorbent material prepared in Example 3 at different temperatures is 18.23-68.34 mg / g, indicating that the renewable CO2 adsorbent material has better adsorption effect under a lower temperature environment. It can also be seen that high temperature is not conducive to the adsorption of CO2 by the renewable CO2 adsorbent material, and high temperature can be used to regenerate the CO2 adsorbent material.

[0077] Example 7 Adsorption effect of regenerable CO2 adsorbent material after regeneration

[0078] S21. Take 1g of the regenerable CO2 adsorbent material prepared in Example 3 and place it in a tubular furnace quartz tube adsorption column. Both ends are blocked with quartz wool. The adsorption temperature is controlled to be 30°C by programming the tubular furnace. A simulated gas (containing 5% CO2 and 95% N2) is introduced. The CO2 content in the outlet gas is analyzed by gas chromatograph. The saturated adsorption amount is calculated. When the CO2 concentration in the tail gas is almost equal to the inlet concentration, the intake is stopped.

[0079] S22. After the air intake is stopped, the temperature in the quartz tube is raised to 250°C within 30 minutes by programming the tube furnace, and after the heating is maintained for 60 minutes, it is cooled to 30°C to obtain the regenerated adsorption material;

[0080] S23. The regenerated adsorbent material was subjected to four repeated adsorption and regeneration experiments;

[0081] S24. Collect and record the saturated adsorption amount of CO2 for 5 times. The results are shown in Table 4.

[0082] Table 4:

[0083] Repetitions Saturated adsorption capacity (mg / g) 0 68.34 1 67.29 2 67.22 3 66.80 4 66.24

[0084] According to the results, the CO2 adsorption capacity of the CO2 adsorbent material after multiple regenerations did not change much. The saturated adsorption capacity of the CO2 adsorbent material decreased from 68.34 mg / g to 66.24 mg / g, an overall decrease of 3.07%.

[0085] In summary, the method provided in the present application can convert the de-oiled residue into a useful CO2 adsorption material at a lower temperature. The obtained CO2 adsorption material has an excellent CO2 adsorption effect, realizing the waste utilization of the de-oiled residue. The regenerated CO2 adsorbent obtained by the regeneration method provided in the present application has an adsorption effect that is not much different from that of a new adsorbent. After multiple regenerations, the adsorption effect of the CO2 adsorbent material can still be ensured to remain at a high level.

[0086] The above is only a preferred embodiment of the present invention. It should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art shall not deviate from the spirit and scope of the present invention, and shall be within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing a renewable CO2 adsorbent material based on deoiled residues of oil-based cuttings from shale gas drilling, characterized in that: The following steps are involved: The de-oiled residue is first ground and sieved, and the sieved powder is collected to obtain the de-oiled residue powder; The de-oiled residue powder is acid-washed and centrifuged using an acid solution to collect an acid precipitate; The acidic precipitate is washed with an alkaline solution until it becomes neutral and then dried to obtain a decontaminated powder; After mixing the impurity-removing powder with sodium hydroxide, a second grinding is performed to obtain an alkali melting reaction system; The alkali-melt reaction system is calcined and cooled to obtain an alkali-melt product; Adding sodium aluminate and deionized water to the alkali-melted product, stirring and standing the product to collect the precipitate; The precipitate is transferred to a reactor for crystallization, washing, suction filtration and drying to obtain the regenerable CO2 adsorption material; Wherein, the weight ratio of the impurity-removing powder to the sodium hydroxide is 1:(1.2-1.4); And / or, the silicon to aluminum ratio in the precipitate is (1-3):

1.

2. The preparation method according to claim 1, characterized in that: The sieving is performed using a 100-mesh sieve.

3. The preparation method according to claim 1, characterized in that: The acid solution comprises a hydrochloric acid solution with a mass fraction of 5% to 10%; And / or, the alkaline solution comprises a sodium hydroxide solution with a mass fraction of 10%.

4. The preparation method according to claim 1, characterized in that: The pickling temperature is 80-85°C and the pickling time is 2h; And / or, the calcination temperature is 550-600°C, and the calcination time is 1-3h; And / or, the crystallization temperature is 90-110° C., and the crystallization time is 8-24 hours; And / or, the stirring time is 16 to 24 hours.

5. The method according to claim 1, characterized in that The amount of the deionized water used is 1.2 to 1.4 times the sum of the mass of the impurity-removing powder and the sodium hydroxide.

6. The regenerable CO2 adsorbent material obtained by the preparation method according to any one of claims 1 to 5.

7. The renewable CO2 adsorbent material prepared by the preparation method according to any one of claims 1 to 5 or the regeneration method of the renewable CO2 adsorbent material according to claim 6, characterized in that: The following steps are involved: The regenerated CO2 adsorbent material is heat-treated at normal pressure to obtain a regenerated CO2 adsorbent material.

8. The regeneration method according to claim 7, characterized in that: The temperature of the heat treatment is 250° C., and the time of the heat treatment is 60 min.

Citation Information

Patent Citations

  • Preparation method and products of zeolite from oil-based drill cuttings pyrolysis ash

    CN108046284B

  • Renewable nano-porous adsorption material for removing carbon dioxide and preparation method of renewable nano-porous adsorption material

    CN114192122A